Perilaku Ekonomi Petani Jambu Mete Di Kecamatan Mawasangka Kabupaten Buton Tengah - Jukasmir Jukasmir; Azhar Bafadal; Ilma Sarimustaqiyma Rianse (Jurnal Sosio Agribisnis, 2022)
The purpose of this study is to determine the economic behavior of cashew farmers, namely production behavior (weeding, pruning, fertilizing and pest and disease control), marketing behavior, saving behavior and investment behavior; and to determine the effect of social and economic factors (age, education level, number of family members, experience and land area) on the economic behavior of cashew farmers. The study was conducted in Mawasangka District, Central Buton Regency, Southeast Sulawesi Province. Determination of the sample of cashew farmers was done by simple random sampling method. The number of samples is 100 farmers. The data were analyzed by multinomial logistic regression. The results of the study indicate that the behavior of cashew farmers in weeding is in the bad category; pruning behavior is categorized as very bad; fertilization behavior is categorized as sufficient, pest and disease control behavior is categorized as not good; marketing behavior is categorized as very bad; saving behavior is categorized as very bad; and investment behavior is categorized as very bad. Social and economic factors (age, education level, farming experience, family dependents and land area) cashew farmers have a positive and significant effect on production behavior, namely weeding, pruning, fertilizing and pest and disease control, except for the number of family dependents that have a positive effect but not significant to fertilization behavior. The factors of age, education level, farming experience, family responsibilities and land area have a positive and significant effect on marketing behavior. Likewise, its influence on investment behavior, all social and economic factors of cashew farmers have a positive and significant effect on investment behavior. While the effect on saving behavior, most of the social and economic factors of farmers have a positive and significant effect on saving behavior, except for the farming experience factor which has a negative but not significant effect.Keywords: economic behavior; social and economic; cashew